Manufacturing and Application of Metalized Ore-Coal Pellets in Synthetic Pig Iron Smelting; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Nokhrina O. I. Olga Ivanovna (2016, 2016)
Title screen